Bioactive ingredients of local garlic variety from Pakis - Ashraf, M; Butt, MS; Ahmad, I; Saeed, MK; Syed, Q; Shah, FH; Shaheen, M (Bangladesh Journal of Scientific and Industrial Research, 2018)
The health claims of locally grown garlic variety/line lehsan gulabi (garlic pink) for the management of serum glucose were explored. In efficacy study, garlic based diets given to the rats i.e. whole garlic (G1), garlic powder (G2) and garlic oil (G3) resulted in reduction in glucose, serum creatinine and serum urea levels, ALT, AST and ALP and elevation in serum insulin as compared to control (G0). The weight of rats substantially suppressed after the intake of different garlic preparations. It is deduced that garlic feeding may prove beneficial in weight management program. The whole garlic consumption proved more effective. The garlic oil caused highest glucose reduction (9.38%). Garlic oil alleviates glucose and insulin related abnormalities more efficiently. Additionally, treatments imparted significant effect on liver and kidney functioning. In the nutshell, pink garlic has potential to curtail different physiological malfunctioning. Thus diet based therapy by selecting suitable food ingredients should be encouraged as a preventive device against various metabolic syndromes among the vulnerable segments in the developing economies. Bangladesh J. Sci. Ind. Res.53(4), 245-252, 2018